If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 8x + 4 Reorder the terms: -2 + 3x = 8x + 4 Reorder the terms: -2 + 3x = 4 + 8x Solving -2 + 3x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 3x + -8x = 4 + 8x + -8x Combine like terms: 3x + -8x = -5x -2 + -5x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -5x = 4 + 0 -2 + -5x = 4 Add '2' to each side of the equation. -2 + 2 + -5x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 4 + 2 -5x = 4 + 2 Combine like terms: 4 + 2 = 6 -5x = 6 Divide each side by '-5'. x = -1.2 Simplifying x = -1.2
| 0.5(12-4s^2)-2s(1-s)=8 | | -(3/5)*(-4) | | z^2-16z+64=0 | | 0.8x+7.7x=-1 | | 9x+9=-189 | | 3x+13=117 | | 5x-40+3x+10=180 | | (5/6y)-(1/6)=7/3 | | 5x+35y=30 | | f(x)=6/5x | | .4(6/20) | | x^3-25x=x-100 | | 0.2(6t+0.7)=9.74 | | 48+112x-16x^2=0 | | f(9.0)=2.8x+7.9 | | 4t(11t+7)=0 | | x+40=3+x | | 8-a/b/16/b | | 17/19=x/19 | | 2x^2+16y-20x+98=0 | | p^2+4p-10=0 | | 11c-16+d= | | 3/4a-16 | | 5x+7=10x-13 | | 3/4a=-16 | | (21b-5)-5(4b+1)=-2 | | 8x+10-y+15y= | | x(y-1)+y(y-1)=0 | | 2(6p+1)+5(p-2)= | | 1435=(3x-10)(x-10)(5) | | p^2+4p+2x-10=0 | | 25=-5/4v |